2012
DOI: 10.1029/2012gc004215
|View full text |Cite
|
Sign up to set email alerts
|

Experimental assessment of the purity of α‐cellulose produced by variations of the Brendel method: Implications for stable isotope (δ13C, δ18O) dendroclimatology

Abstract: [1] Stable isotope dendroclimatology using a-cellulose has unique potential to deliver multimillennial-scale, sub-annually resolved, terrestrial climate records. However, lengthy processing and analytical methods often preclude such reconstructions. Variants of the Brendel extraction method have reduced these limitations, providing fast, easy methods of isolating a-cellulose in some species. Here, we investigate application of Standard Brendel (SBrendel) variants to resinous soft-woods by treating samples of k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 63 publications
1
23
1
Order By: Relevance
“…Individual rings for both species, corresponding to the years 2000-2010 (plus latewood from 1999), were visually inspected under a microscope to locate ring boundaries and the position of the earlywoodlatewood transition. Micro-slicing was conducted using a sledge microtome with a target mass of 1.5 mg for extraction of α-cellulose for δ 18 O, which is considered to be the most useful component of wood for this analysis because of its inability to isotopically exchange with other compounds (Wright, 2008;Brookman and Whittaker, 2012). The extraction procedure followed the modified Brendel (mBrendel) method (Gaudinski et al, 2005), adapted for small sample sizes (Evans and Schrag, 2004 ‰).…”
Section: Sample Preparation and Oxygen Isotope Analysesmentioning
confidence: 99%
“…Individual rings for both species, corresponding to the years 2000-2010 (plus latewood from 1999), were visually inspected under a microscope to locate ring boundaries and the position of the earlywoodlatewood transition. Micro-slicing was conducted using a sledge microtome with a target mass of 1.5 mg for extraction of α-cellulose for δ 18 O, which is considered to be the most useful component of wood for this analysis because of its inability to isotopically exchange with other compounds (Wright, 2008;Brookman and Whittaker, 2012). The extraction procedure followed the modified Brendel (mBrendel) method (Gaudinski et al, 2005), adapted for small sample sizes (Evans and Schrag, 2004 ‰).…”
Section: Sample Preparation and Oxygen Isotope Analysesmentioning
confidence: 99%
“…Carbon-isotope determinations were made on annual rings dated from 1983-2009 (sliced from 18 cores from 7 trees, using a razor blade) as a pilot investigation to determine the potential for further studies (see Brookman 2014). The rings were processed to α-cellulose using the Brendel method (Brendel et al 2000) modified for small samples (Evans and Schrag 2004) and specifically for kauri, which appears to require more intensive extraction techniques than other resinous conifers (Brookman and Whittaker 2012). Brookman (2014) further identifies potential complications for δ 13 C extraction using the SBrendel method, which may result in small inter-annual discrepancies between real and measured values.…”
Section: Methodsmentioning
confidence: 99%
“…Robertson 1997a, b;McCarroll and Pawellek 2001;Porter et al 2009). The most likely reason for this is considered to be a combination of the sensitivity of young trees to micro-scale endogenous influences and the difficulties of processing kauri wood to α-cellulose (Brookman and Whittaker 2012;Brookman 2014).…”
mentioning
confidence: 99%
“…Brendel et al put forward a revised technique for α‐cellulose extraction from wood, which was improved for smaller samples by Evans and Schrag . Unfortunately, the process of extracting the cellulose molecules from the rest of the leaf tissues involves chemical and physical processes which may facilitate oxygen isotope fractionation or even the exchange of oxygen within the cellulose with the oxygen in the reagents used . It is therefore important to test a potential cellulose extraction technique before employing it to retrieve data for palaeoclimate studies.…”
Section: Introductionmentioning
confidence: 99%
“…Brookman and Whittaker observed that not all plant species and tissue types react in the same way to the cellulose extraction process. It was discovered that by varying the temperature, reagent amount and extraction time, the δ 18 O values of the resultant α‐cellulose could be altered significantly, and by differing degrees dependent on species and tissue type.…”
Section: Introductionmentioning
confidence: 99%